2019
DOI: 10.1158/0008-5472.can-18-2867
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery ofOx40l,Cd80, andCd86mRNA Kindles Global Anticancer Immunity

Abstract: Localized expression of effector molecules can initiate antitumor responses through engagement of specific receptors on target cells in the tumor microenvironment. These locally induced responses may also have a systemic effect, clearing additional tumors throughout the body. In this study, to evoke systemic antitumor responses, we utilized charge-altering releasable transporters (CART) for local intratumoral delivery of mRNA coding for costimulatory and immune-modulating factors. Intratumoral injection of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 47 publications
0
98
1
Order By: Relevance
“…1) that are effective for the delivery of mRNA and pDNA to a variety of cell types in cell culture and live animals. 33,[45][46][47][48][49] These cationic amphiphilic oligomers, when complexed with negatively-charged oligonucleotides, form polyelectrolyte complexes that exhibit dynamic, charge-altering behavior that facilitates the intracellular release of the oligonucleotides. 33 This dynamic charge-altering behavior was attributed to the unique structural features of the cationic a-aminoester sequences 44 of these amphiphilic oligomers which exhibit a pH-dependent selective degradation to neutral diketopiperazines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) that are effective for the delivery of mRNA and pDNA to a variety of cell types in cell culture and live animals. 33,[45][46][47][48][49] These cationic amphiphilic oligomers, when complexed with negatively-charged oligonucleotides, form polyelectrolyte complexes that exhibit dynamic, charge-altering behavior that facilitates the intracellular release of the oligonucleotides. 33 This dynamic charge-altering behavior was attributed to the unique structural features of the cationic a-aminoester sequences 44 of these amphiphilic oligomers which exhibit a pH-dependent selective degradation to neutral diketopiperazines.…”
Section: Discussionmentioning
confidence: 99%
“…44 We have leveraged this behavior in the design of novel cationic amphiphilic oligomers, charge-altering releasable transporters (CARTs), 33,[45][46][47] that bind, complex, and deliver oligonucleotides of wide ranging size (mRNA, pDNA) into cells, in vitro and in vivo. 33,[45][46][47][48][49] At low pH, these oligomeric amphiphiles are cationic and associate in water with polyanionic oligonucleotides to form polyelectrolyte complexes. At elevated pH these polyelectrolyte complexes release the oligonucleotides, which was attributed to the charge-altering degradative behavior of the cationic oligo(aamino ester)s (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, through high-throughput screening, we previously discovered that CARTs containing both unsaturated C18 oleyl and C9 nonenyl lipids (CART O 5 :N 6 :A 9 ( 2 ), CART BDK-O 7 :N 7 :A 13 ( 3 )) resulted in enhanced transfection of T and B lymphocytes, significantly outperforming single-lipid CARTs and commercial reagents 41 . In fact, these mixed-lipid CARTs resulted in >80% transfection of immortalized T lymphocytes in vitro 41 as well as ≥1.5% in vivo in living mice when administered intravenously 46,52 , significantly outperforming previous transfection technologies for mRNA delivery into T lymphocytes 41,5355 . We therefore hypothesized that CARTs may represent a novel delivery vector for highly transfection-recalcitrant resting NK cells.…”
Section: Resultsmentioning
confidence: 96%
“…Further studies will need to examine whether sufficient numbers of CART-generated CAR NK cells can be readily generated, and to assess their lifespan in vivo in order to determine if this technique would be superior to lentiviral transduction for CAR NK cell preparation. As we have previously demonstrated that CARTs can be used to deliver mRNA in vivo with a high specificity for mRNA expression in the spleen 41,46,52 , in vivo CART-mediated delivery of CAR-encoding mRNA may provide an alternative therapeutic approach for the generation of CAR NK cells as a strategy for personalized cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%